2017
DOI: 10.1149/2.1461707jes
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of PEMFC Electrodes from Milligram-Amounts of Catalyst Powder

Abstract: Development of electrocatalysts with higher activity and stability is one of the highest priorities in enabling cost-competitive hydrogen-air fuel cells. Although the rotating disk electrode (RDE) technique is widely used to study new catalyst materials, it has been often shown to be an unreliable predictor of catalyst performance in actual fuel cell operation. Fabrication of membraneelectrode assemblies (MEA) for evaluation which are more representative of actual fuel cells generally requires relatively large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 42 publications
3
45
0
Order By: Relevance
“…The variation in the intermolecular forces at the metastable zone of nucleation growth by the presence of an additional concentration of metals may be the driving cause for the variation in particle size. Similar results were observed by Antolini [ 89 ] and Yarlagadda et al [ 90 ].…”
Section: Particle Size Control Aspects Of Microreactor During Syntsupporting
confidence: 91%
“…The variation in the intermolecular forces at the metastable zone of nucleation growth by the presence of an additional concentration of metals may be the driving cause for the variation in particle size. Similar results were observed by Antolini [ 89 ] and Yarlagadda et al [ 90 ].…”
Section: Particle Size Control Aspects Of Microreactor During Syntsupporting
confidence: 91%
“…15 In the present work, the catalyst film on the GDL (i.e. the GDE) is prepared by vacuum filtration as described by Yarlagadda et al 21 4 In the SI it is demonstrated that with the established procedure, reproducible particle size distributions of the different Pt/C catalysts could be determined before ( Figure S5) as well as after the ASTs (Figure S6). The same reproducibility is observed for the determined values of the electrochemically active surface area (ECSA), see relatively low standard deviations from the measurements of three catalyst films in Table 1.…”
Section: Resultsmentioning
confidence: 85%
“…The Sigracet 39BC gas diffusion layer (GDL) was placed in a vacuum filtration setup between a glass funnel and a sand core filter. All this was placed on a collecting bottle as described by Yarlagadda et al 21 . 4 mL of the inks were diluted with mL of Milli-Q water and 29 mL of IPA (water-IPA ratio of 1:3, Pt concentration of 0.05 mg L -1 ).…”
Section: Vacuum Filtration and Pressing Of Gdementioning
confidence: 99%
“…To prepare the catalyst films, a cylindrical reservoir with a cross-sectional area of 10.75 cm 2 was placed on top of the gas diffusion layer (GDL) with an MPL (Sigracet 39BC), which was positioned onto a sand core filter. All this was placed on a collecting bottle, as described by Yarlagadda et al 23 . The reservoir was filled with 20 mL of ink and a vacuum was applied with the help of a water jet pump.…”
Section: Working Electrode Preparationmentioning
confidence: 99%